Ecological restoration policy should pay more attention to the high productivity grasslands. (October 2021) - Yan, Huimin; Xue, Zhichao; Niu, Zhongen
Highlights: Discriminate the impacts of human activities on grassland productivity dynamics. Ecological restoration improved vegetation activity in eco-fragile grasslands. Higher productivity grasslands are facing with degradation by livestock growing. Region-based foreseeable grassland management is needed before degradation appears. Abstract: To address severe grassland degradation problems, China has been implementing several national restoration programs, which have been reported to mitigate the deterioration of grassland ecosystem function. However, the regional differences in the effectiveness of the programs are not yet known. In this study, gross primary productivity (GPP) was selected as an indicator to analyze grassland degradation dynamics, and the residual trend method was used to assess the driving force of grassland degradation based on GPP. The results showed the GPP of Inner Mongolia grassland significantly increased by 3.94 g C m −2 yr −1 during 2000–2015, climate change was the dominant driving factors, while human activities slightly reduced grassland productivity (−0.17 g C m −2 yr −1 ). But there are obviously spatial heterogeneous on the impact of human activities. Specifically, grassland management significantly promoted the GPP increase in semidesert steppe, while grazing activity decreased the GPP in meadow and typical steppes. These findings suggest that ecological restoration programs could obviously improve vegetation functioning in ecologically fragile grassland which has relatively very low productivity. However, the grasslands with relative higher productivity or initially non-degraded are still facing with great degradation risk due to the continuous growing livestock scale. Therefore, p olicy-makers should pay more attention to the originally non-degraded or high productivity grasslands, especially at those years the negative impacts of intensive grazing could be concealed by the well-growth grass under abundant precipitation.